Immigration Labor and Workplace Safety - Thomas K. Bauer; Andreas Million; Ralph Rotte; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 1998)
Using standard as well as recently developed univariate and bivariate count data models, this paper analyzes the determinants of workplace accidents using a firm data set for Germany. Given the tight system of public workplace safety regulation, introduced partly as early as in 1869, and the important role of foreign labor in manufacturing, the focus is on the impact of work organization and interdependence between native and foreign workers. The empirical results indicate that there are no significant differences between natives and foreign workers regarding technological determinants of workplace accidents. However, the employment of guestworkers has a strong positive effect on the job safety of natives. The estimates imply that a 1 percent increase in the employment of guestworkers is associated with a 0.4 percent decrease of severe accidents of natives.
Keywords: C25; L60; J28; C35; 330; Workplace accidents; industrial organization; labor relations; immigration; count data models; Arbeitsschutz; Arbeitsunfall; Ausländische Arbeitskräfte; Schätzung; Deutschland